Investigation of water flow window with/without energy storage tank during winter season - Yamac, Halil Ibrahim; Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2023)
The Water Flow Window (WFW) system includes water circulation in the gap between glazing. This circulation takes away the undesirable heat. What if this waste heat is stored? This concept can affect the electricity con-sumption of the Heating Ventilating and Air Conditioning (HVAC) devices. The WFW system's performance analysis with/without an energy storage tank during the winter is investigated in this study's scope. The ex-periments are conducted in Turkey's natural winter environment. Three identical testing cabinets have different glazing types; these are standard (air-filled) windows (SW)s and WFW with/without energy storage tanks are used. The test cabinets' HVAC devices' electricity consumption is compared. A water tank includes two different Phase Change Materials (PCM)s called Thermal Energy Storage (TES) tank. PCMs are placed around and stuffed tubes as pistol-type inside water. The PCM-TES tank volume includes 2.4 L of water; PCMs are 2.6 L RT18 HC and 0.7 L RT22 HC. The numerical analysis is made to visualize water temperature between glazing in the ANSYS Fluent with Volume of Fluid (VOF) method. It is seen that the ratio of electricity consumption with/without energy storage tank WFWs to SWs drops to 27% for daytime; 45% for nighttime. The minimum flow rate of HTF in the WFW with PCM-TES tank results has the lowest consumption ratio. The thermal energy is stored for 8 h and used for 12 h. 60% of the stored energy can be recovered.
Keywords: Multiphase Computational Fluid Dynamics; Water Flow Window; Solar Energy Storage; Phase Change Material